2014
DOI: 10.1007/s00128-014-1374-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Tolerance and Zinc Removal Ability of Living and Dried Biomass of Desmodesmus communis

Abstract: Effects of zinc on growth, cell morphology, oxidative stress, and zinc removal ability of the common phytoplankton species Desmodesmus communis were investigated at a concentration range of 0.25-160 mg L(-1) zinc. Cell densities and chlorophyll content decreased in treated cultures, changes in coenobia morphology and elevated lipid peroxidation levels appeared above 2.5 mg L(-1) zinc. The most effective zinc removal was observed at 5 mg L(-1) zinc concentration, while maximal amount of removed zinc appeared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…C. sorokiniana exhibited high Zn tolerance, and higher total Zn content, probably because of its high Zn absorption capacity. The biosorption capacity of C. sorokiniana appears to be much higher than that of D. communis (Novák et al, 2014), M. pusillum and M. griffithii (Bácsi et al, 2014), which are reported to be good Zn biosorbents. Therefore, application of a resistant algal species for the purification of wastewater offers a high potential and a cheap strategy for removal of toxic metal ions from polluted water bodies.…”
Section: Zn Metal Biosorption Capacitymentioning
confidence: 88%
See 3 more Smart Citations
“…C. sorokiniana exhibited high Zn tolerance, and higher total Zn content, probably because of its high Zn absorption capacity. The biosorption capacity of C. sorokiniana appears to be much higher than that of D. communis (Novák et al, 2014), M. pusillum and M. griffithii (Bácsi et al, 2014), which are reported to be good Zn biosorbents. Therefore, application of a resistant algal species for the purification of wastewater offers a high potential and a cheap strategy for removal of toxic metal ions from polluted water bodies.…”
Section: Zn Metal Biosorption Capacitymentioning
confidence: 88%
“…Studies investigating microalgae responses to Zn stress, have so far mostly addressed changes in growth and metal accumulation (Omar 2002;Bácsi et al, 2014;Dinesh, et al, 2014;Novák et al, 2014). Comparatively, less is known on the effects of Zn in C. sorokiniana and S. acuminatus, at the biochemical level.…”
Section: Zn Stress Inhibits Growth and Induces Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, quantitative variables of biological communities in sewage water storage facilities are higher than in water bodies polluted only by surface runoff (Krupa, 2012;Barinova, Krupa & Romanova, 2018). Effective purification of sewage water storage facilities occurs due to the biological activity of unicellular algae which accumulation of heavy metals by cell surface (Fargašova, Bumbálová & Havránek, 1997;Macfie & Welbourn, 2000;Novák, Jánószky, B-Béres, Nagy & Bácsi 2014;Bácsi et al, 2015) more intensively compared to that of macrophytes and ichthyofauna (Chizhikova, Sirotsky, Kharitonova & Utkina, 2011;Niemiec, Szeląg-Sikora, Sikora, Cupiał & Komorowska, 2018).…”
Section: Metalmentioning
confidence: 99%